A critical comparison between the semisitting and the supine positioning in vestibular schwannoma surgery: Subgroup analysis of a randomized, multicenter trial - Scheller, Christian; Rampp, Stefan; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver; Bischoff, Barbara; Matthies, Cordula; Westermaier, Thomas; Pedro, Maria Teresa; Rohde, Veit; von Eckardstein, Kajetan; et al. (Journal of Neurosurgery, 2020)
OBJECTIVE Patient positioning in vestibular schwannoma (VS) surgery is a matter of ongoing discussion. Factors to consider include preservation of cranial nerve functions, extent of tumor resection, and complications. The objective of this study was to determine the optimal patient positioning in VS surgery. METHODS A subgroup analysis of a randomized, multicenter trial that investigated the efficacy of prophylactic nimodipine in VS surgery was performed to investigate the impact of positioning (semisitting or supine) on extent of resection, functional outcomes, and complications. The data of 97 patients were collected prospectively. All procedures were performed via a retrosigmoid approach. The semisitting position was chosen in 56 patients, whereas 41 patients were treated while supine. RESULTS Complete resection was obtained at a higher percentage in the semisitting as compared to the supine position (93% vs 73%, p = 0.002). Logistic regression analysis revealed significantly better facial nerve function in the early postoperative course in the semisitting group (p = 0.004), particularly concerning severe facial nerve paresis (House-Brackmann grade IV or worse; p = 0.002). One year after surgery, facial nerve function recovered. However, there was still a tendency for better facial nerve function in the semisitting group (p = 0.091). There were no significant differences between groups regarding hearing preservation rates. Venous air embolism with the necessity to terminate surgery occurred in 2 patients in the semisitting position (3.6%). Supplementary analysis with a 2-tailed permutation randomization with 10,000 permutations of treatment choice and a propensity score matching showed either a tendency or significant results for better facial nerve outcomes in the early postoperative course and extent of resection in the semisitting group. CONCLUSIONS Although the results of the various statistical analyses are not uniform, the data indicate better results concerning both a higher rate of complete removal (according to the intraoperative impression of the surgeon) and facial nerve function after a semisitting as compared to the supine position. These advantages may justify the potential higher risk for severe complications of the semisitting position in VS surgery. The choice of positioning has to consider all individual patient parameters and risks carefully.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Acoustic neuroma; Facial nerve; Semisitting position; Supine position; Vestibular schwannoma

Anatomy and microsurgical relevance of the outer arachnoid envelope around the olfactory bulb based on endoscopic cadaveric observations - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Adib, Sasan Darius; Barany, Laszlo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background: Surgical approaches to the anterior cranial fossa have great risk of damaging the olfactory tract and bulb. The goal of this study was to describe the outer arachnoid envelope around the olfactory bulb which plays significant role in the approach-related injury of the nerve. Material and Methods: A total of 20 fresh human cadaveric heads were examined as a following: 5 cadaveric heads were used to describe a gross overview of the topographic anatomy of the outer arachnoid cover of the olfactory bulb. In 15 cadaveric heads endoscopic surgical approaches were performed to examine the in situ undisrupted anatomy of the outer arachnoid around the olfactory bulb. Four cadaveric heads were used for lateral subfrontal approach, 5 heads for medial subfrontal, 3 heads for median subfrontal approach and 3 heads for anterior interhemispheric approach. Results: The outer arachnoid membrane of the frontal lobe attaches the olfactory bulb strongly to the above lying olfactory sulcus. Only the most rostral portion of the olfactory bulb became slightly detached from the frontal lobe. The outer arachnoid forms a decent protrusion around the tip of the olfactory bulbs. The fila olfactoria have their own outer arachnoid cover as a continuation of the same layer of the olfactory bulb. The effect of brain retraction and manipulation forces on the olfactory bulb and the role of the here located arachnoid membranes were visually analysed and described in detail through the performed four different neurosurgical approaches. Conclusion: The results of our observations provide important anatomical details for the preservation of smelling during neurosurgical procedures.
CRIS-Team Scopus Importer:2024-12-16
Keywords: arachnoid membranes; endoscopic anatomy; microsurgical anatomy; olfactory bulb

Angiographic CT with intravenous contrast agent application for monitoring of intracranial flow diverting stents - Saake, Marc; Struffert, Tobias; Gölitz, Philipp; Ott, Sabine; Seifert, Frank; Ganslandt, Oliver; Dörfler, Arnd (Neuroradiology, 2012)
Introduction: Intracranial flow diverting devices are increasingly used to treat cerebral aneurysms. A reliable, noninvasive follow-up modality would be desirable. Our aim was to compare intra-arterial digital subtraction angiography (ia DSA) to angiographic computed tomography with intravenous contrast agent application (iv ACT) in the visualisation of flow diverting devices and aneurysm lumina. Methods: Follow-up monitoring by iv ACT (n=36) and ia DSA (n=25) in 14 patients treated with flow diverting devices for intracranial aneurysms was evaluated retrospectively. Images were evaluated by two neuroradiologists in anonymous consensus reading regarding the device deployment, wall apposition, neck coverage of the aneurysm, opacification of the vessel and device lumen, as well as the degree of aneurysm occlusion. Results: Corresponding ia DSA and iv ACT images were scored identically in all patients regarding the stent deployment, wall apposition and neck coverage, as well as the degree of aneurysm occlusion and patency status of the device and parent artery. Opacification of the parent vessel lumen and perfused parts of the aneurysm was considered slightly inferior for iv ACT in comparison with ia DSA (seven of 36 cases), without impact on diagnosis. Conclusions: We demonstrated the feasibility and diagnostic value of iv ACT in follow-up imaging of intracranial flow diverting devices. Due to its high spatial resolution and non-invasive character, this novel technique might become a valuable imaging modality in these patients. © Springer-Verlag 2011.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiography; Computed tomography; Flat detector; Flow diverting stent; Follow-up; Intravenous

Angiographic CT with intravenous contrast injection compared with conventional rotational angiography in the diagnostic work-up of cerebral aneurysms - Gölitz, Philipp; Struffert, Tobias; Knossalla, F.; Saake, Marc; Ott, Sabine; Ganslandt, Oliver; Dörfler, Arnd (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Noninvasive imaging of cerebral aneurysms is still considered inferior to conventional angiography. The purpose of this study was to evaluate the diagnostic accuracy of ivACT in the assessment of intracranial aneurysms compared with 3D-DSA. MATERIALS AND METHODS: We included 13 patients with 15 incidental unruptured saccular aneurysms scheduled for diagnostic angiographic work-up in our study. In each patient, we performed an ivACT and a conventional angiography including a 3D rotational run. During postprocessing, MPR images were generated for each technique. Maximal aneurysm diameter, neck diameter, aneurysm height, maximum width, bulge height, parent artery diameter, and angle between the parent artery and aneurysm apex were measured for each aneurysm. RESULTS: 3D-DSA and ivACT both provided images of high quality without artificial disturbances (ie, motion artifacts). Measurements of all parameters resulted in comparable values for both modalities with a strong correlation (P ≤ .001). CONCLUSIONS: ivACT is feasible for the noninvasive visualization of saccular cerebral aneurysms and may provide reliable diagnostic information for the assessment of aneurysm size and geometry comparable with conventional intra-arterial 3D rotational angiography. These preliminary results might be a first promising step to replacing conventional angiography in preinterventional aneurysm imaging.
CRIS-Team Scopus Importer:2022-08-05

Arachnoid Membranes Around the Cisternal Segment of the Trigeminal Nerve: A Cadaveric Anatomic Study and Intraoperative Observations During Minimally Invasive Microvascular Decompression Surgery - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Barany, Laszlo (World Neurosurgery, 2019)
Objective: The minimally invasive microvascular decompression (MVD) for trigeminal neuralgia is technically a more challenging operation compared with the standard retrosigmoidal approach. Endoscopic assistance could help to widen the field of view of the microscope during MVD. An extended view around the cisternal segment of the trigeminal nerve can be achieved only with the targeted dissection of the arachnoid membranes. The goal of our study was to analyze the three-dimensional organization of these membranes around the trigeminal nerve. Methods: Microsurgical, endoscopic, and macroscopic anatomic examinations were performed on 50 fresh human cadaveric specimens. Retrospective analysis of the video documentations of 50 MVDs was performed to describe the surgical relevance of the examined membranes. Results: The trigeminal nerve is surrounded circumferentially by 4 inner arachnoid membranes: laterally and caudally by the trigeminal membrane (TM), cranially by the superior cerebellar membrane (SCM), and medially by the junction between the cranial edge of the anterior pontine membrane and the lateral edge mesencephalic leaf of the Liliequist membrane complex. The superior cerebellar artery was located in every case cranial from the SCM. This membrane served as a safety plane to dissect the vessel from the nerve. The SCM was laterally adherent to the TM, which made the arachnoid dissection challenging. The superior petrosal vein was located cranially and laterally from the described inner arachnoid membranes, but the transverse pontine vein was embedded into the membrane complex. Conclusions: Knowledge of the described anatomy of the arachnoid membranes around the trigeminal nerve is essential to safely perform an MVD.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Arachnoid membranes; Endoscopic anatomy; Microvascular decompression; Posterior fossa; Retrosigmoid keyhole approach; Trigeminal nerve; Trigeminal neuralgia

Cerebral aneurysm treatment using flow-diverting stents: in-vivo visualization of flow alterations by parametric colour coding to predict aneurysmal occlusion: preliminary results - Gölitz, Philipp; Struffert, Tobias; Roesch, Julie; Ganslandt, Oliver Thomas; Knossalla, Frauke; Dörfler, Arnd (European Radiology, 2015)
After deployment of flow-diverting stents (FDS), complete aneurysm occlusion is not predictable. This study investigated whether parametric colour coding (PCC) could allow in vivo visualization of flow alterations induced by FDS and identify favourable or adverse flow modulations.Thirty-six patients treated by FDS were analyzed. Preinterventional and postinterventional DSA-series were postprocessed by PCC and time-density curves (TDCs) were calculated. The parameters aneurysmal inflow, outflow, and relative time-to-peak (rTTP) were calculated. Preinterventional and postinterventional values were compared and related to occlusion rate.Postinterventional inflow showed a mean reduction of 37%, outflow of 51%, and rTTP a prolongation of 82%. Saccular aneurysm occlusion occurred if a reduction of at least 15% was achieved for inflow and 35% for outflow (sensitivity: 89%, specificity: 82%). Unchanged outflow and a slightly prolonged rTTP were associated with growth in one fusiform aneurysm.PCC allows visualization of flow alterations after FDS treatment, illustrating "flow diverting effects" by the TDC shape and indicating mainly aneurysmal outflow and lesser inflow changes. Quantifiable parameters (inflow, outflow, rTTP) can be obtained, thresholds for predicting aneurysm occlusion determined, and adverse flow modulations assumed. As a rapid intraprocedural tool, PCC might support the decision to implant more than one FDS.o After deployment of a flow-diverting stent, complete aneurysm occlusion is unpredictable. o Parametric colour coding offers new options for visualizing in vivo flow alterations non-invasively. o Quantifiable parameters, i.e., aneurysmal inflow/outflow can be obtained allowing prognostic stratification. o Rapid, intraprocedural application allows treatment monitoring, potentially contributing to patient safety.
EVALuna2:22356

Characterization of a Factual Knowledge-Associated Brain Memory Area by Functional Magnetic Resonance Imaging and Implementation in Tumor and Epilepsy Brain Surgery - Grummich, Peter; Ganslandt, Oliver Thomas; Buchfelder, Michael; Roessler, Karl (World Neurosurgery, 2017)
BACKGROUND: The role of the dominant hippocampus in verbal and episodic memory recall has been extensively investigated. However, there are categories of memory estimated independent of hippocampal function. In particular, factual knowledge is solely constituted from written or spoken input independent on undertaken experience, but the temporal structures involved are not well defined. METHODS: In this retrospective study, we mapped the activity of factual knowledge recall using functional magnetic resonance imaging (fMRI) in 60 patients scheduled for tumor or epilepsy surgery and in 18 patients resected within or close to the left mesial temporal lobe. Memory tests were performed preoperatively and postoperatively to investigate deficit symptoms in factual knowledge retrieval. RESULTS: We found a highly reproducible localized brain area within the parahippocampal gyrus, in the depth of the dorsal collateral sulcus, which was constantly involved in factual knowledge retrieval during fMRI tasks in 93% of patients (56/60) during recall of capital cities or multiplication tasks, in two thirds of the patients mainly on the dominant side. In addition, all 18 patients after surgery within this area showed postoperative factual knowledge deficits (56% permanent, 44% transitory), memory prognosis significantly correlating with the first day's factual knowledge retrieval task results. CONCLUSIONS: Using fMRI, we visualized a circumscribed brain area within the parahippocampal gyrus during factual knowledge retrieval, the lesioning of which led to factual knowledge deficits. Thus, impairment of factual knowledge retrieval may occur if resection is extended into the parahippocampal gyrus. Preoperative fMRI memory maps may contribute to avoiding such deficits.
EVALuna2:102195

Combined Laser-Doppler Flowmetry and Spectrophotometry: Feasibility Study of a Novel Device for Monitoring Local Cortical Microcirculation during Aneurysm Surgery - Sommer, Bjoern; Kreuzer, Maximilian; Bischoff, Barbara; Wolf, Dennis; Schmitt, Hubert; Eyüpoglu, Ilker Yasin; Roessler, Karl; Buchfelder, Michael; Ganslandt, Oliver Thomas; Wiendieck, Kurt (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Monitoring of cortical cerebral perfusion is essential, especially in neurovascular surgery. Study Aims To test a novel noninvasive laser-Doppler flowmetry and spectrophotometry device for feasibility during elective cerebral aneurysm surgery. Material and Methods In this prospective single-institution nonrandomized trial, we studied local cerebral microcirculation using the noninvasive laser-Doppler spectrophotometer "Oxygen-to-see" (O2C) in 20 consecutive patients (15 female, 5 male; median age: 60.5 ± 11.7 years) who were operated on for incidental cerebral aneurysms. Capillary-venous oxygenation (oxygen saturation ["SO2"]), postcapillary venous filling pressures (relative hemoglobin content ["rHb"]), blood cell velocity ("velo"), and blood flow ("flow") were measured in 7-mm tissue depth using a subdural fiberoptic probe. Results Representative recordings were acquired immediately after dural opening over a median time span of 88 ± 21.8 seconds (range: 60-128 seconds) before surgical manipulation. Baseline values (median ± 2 standard deviations) of brain perfusion as measured with the O2C device were SO2, 39 ± 16.6%; rHb, 53 ± 18.6 arbitrary units (AU); velo, 60 ± 20.4 AU; and flow, 311 ± 72.8 AU. Placement of the self-retaining retractor led to a decrease in SO2 of 17% ± 29% (p < .05) and flow of 10% ± 11% (p < .01); rHb increased by 18% ± 20% (p < .01), and velo remained unchanged. Retractor removal caused the opposite with an increased flow of 10% ± 7% (p < 0.001) and velo (3% ± 6%, p = 0.11), but a decrease in SO2 of 24% ± 33% (p = 0.09) and rHb of 12% ± 20% (p =0.18). No neurologic or surgical complications occurred. Conclusion Using this novel noninvasive system, we were able to measure local cerebral microcirculation during aneurysm surgery. Our data indicate that this device is able to detect changes during routine neurosurgical maneuvers. Thus it may be useful for early detection of cerebral microcirculatory disturbance
EVALuna2:16739

Comparison of the Ramirez technique for the closure of large open myelomeningocele defects with alternative methods - Kneser, Ulrich; Bigdeli, Amir K.; Himmler, Joerg P.; Eyüpoglu, Ilker Yasin; Ganslandt, Oliver Thomas; Hirsch, Almut; Schmidt, Volker J.; Beier, Justus; Horch, Raymund E. (Journal of Plastic Reconstructive and Aesthetic Surgery, 2015)
To compare the Ramirez technique for the operative closure of large open myelomeningocele defects with conventional closure techniques in newborns. We hypothesized that the immediate surgical treatment with the Ramirez technique is superior to prior used operative techniques.From 2003 to 2010, 23 children (8 female, 15 male) underwent closure of large open myelomeningocele defects using the Ramirez technique (group A), while from 1993 to 2002, 23 children (6 female, 17 male) underwent conventional closure techniques (group B). All children were included in the retrospective analysis with a mean follow-up period of 3.4 years.Perioperative variables were similar in both groups (P = ns). There were no hospital deaths in both groups. The operation time was significantly higher in group A (228.7 ± 76.8 versus 157.8 ± 70.3 min, P = 0.003). Mean length of hospital stay was significantly lower in group A (30.7 ± 16.4 days versus 52.0 ± 38.5; P = 0.02). Postoperative complication rate was significantly lower in group A (P = 0.01). Beyond postoperative day 10, liquor fluid leakage was significantly lower in group A (P = 0.05). During follow-up, there were no complications in group A. In group B, 2 children developed liquor fistulas.The Ramirez technique allows efficient and safe closure of large open myelomeningocele defects and reduces incidence of postoperative liquor fistulae. The increased operation time and surgical efforts seem to be justified. Treatment of large myelomeningocele defects requires an interdisciplinary team including paediatrician-neonatologists, neurosurgeons and plastic surgeons.
EVALuna2:15600

Contrast-enhanced angiographic computed tomography for detection of aneurysm remnants after clipping: a comparison with digital subtraction angiography in 112 clipped aneurysms - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver Thomas; Lang, Stefan; Knossalla, Frauke; Dörfler, Arnd (Neurosurgery, 2014)
For preclusion of remnants after aneurysm clipping, a reliable, noninvasive imaging technique is desirable.To evaluate the reliability of optimized angiographic computed tomography with intravenous contrast agent injection (ivACT) in detecting remnants after aneurysmal clipping compared with digital subtraction angiography (DSA), the gold standard.We included 84 patients with 112 clipped cerebral aneurysms of the anterior circulation. For treatment, 116 clips of cobalt and 57 clips of titanium alloy were used. In each patient, we performed an ivACT with dual rotational acquisition and a DSA. Data from ivACT were postprocessed with a dual-volume technique with newly implemented reconstructions modes. Aneurysm remnants were measured, classified, and correlated with DSA by 2 raters.In total, 12 remnants were revealed by DSA, meaning a prevalence of 11%. IvACT demonstrated a sensitivity of 75% to 92% and a specificity of 99% in detecting remnants up to a minimal size of 0.7 × 0.3 mm. Classification of remnants by ivACT was identical to that by DSA, and assessment of size showed a significant correlation with DSA (P < .001). No significant differences between cobalt and titanium alloy were revealed concerning artifacts.Optimized ivACT with enhanced postprocessing demonstrated high sensitivity and specificity in detecting remnants after aneurysm clipping in the anterior circulation. Classification and assessment of remnant size and detection of relevant parent artery stenosis showed high accuracy of ivACT compared with DSA. Our results indicate that ivACT might become a noninvasive alternative to DSA for postsurgical control.
EVALuna2:22328

Differences in metabolism of fiber tract alterations in gliomas: A combined fiber density mapping and magnetic resonance spectroscopic imaging study - Stadlbauer, Andreas; Hammen, Thilo; Buchfelder, Michael; Bachmair, Johanna; Dörfler, Arnd; Nimsky, Christopher; Ganslandt, Oliver (Neurosurgery, 2012)
BACKGROUND: Gliomas propagate diffusely throughout and along white matter structures. Glioma-related changes in structural integrity and metabolism are not detectable by standard magnetic resonance (MR) imaging. OBJECTIVE: To investigate differences in the metabolism of fiber tract alterations between gliomas grade II to IV by correlation of fiber density values with metabolite concentrations measured by fiber density mapping and MR spectroscopic imaging. METHODS: Fiber density mapping and MR spectroscopic imaging were performed in 48 patients with gliomas WHO grade II to IV. Fiber density mapping data were used to define fiber tracts in tumoral and peritumoral areas. Structural integrity of fiber tracts was assessed as fiber density ipsilateral-to-contralateral ratio (FD ICR). Metabolite concentrations for choline-containing compounds and N-acetyl-aspartate were computed and correlated to FD ICR values after coregistration with anatomic MR imaging. RESULTS: In tumoral areas, choline-containing compound concentrations of altered fiber tracts were significantly different between low- and high-grade glioma and showed different courses for the correlations of FD ICR and choline-containing czeompounds. In high-grade glioma, increasing fiber destruction was associated with a massive progression in cell membrane proliferation. Peritumoral fiber structures showed significantly decreased N-acetyl-aspartate concentrations for all patients, but only patients with glioblastoma multiforme had significantly decreased fiber density compared with the contralateral side. Glioma grades II and III had significantly higher peritumoral FD ICR than glioblastoma multiforme. CONCLUSION: A multiparametric MR imaging strategy providing information about both structural integrity and metabolism of the tumor is required for detailed assessment of glioma-related fiber tract alterations, which in turn is essential for treatment planning. Copyright © 2012 by the Congress of Neurological Surgeons.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain tumor; Diffusion tensor; Fiber density; Magnetic resonance spectroscopy

Differentiation of Glioblastoma and Brain Metastases by MRI-Based Oxygen Metabolomic Radiomics and Deep Learning - Stadlbauer, Andreas; Heinz, Gertraud; Marhold, Franz; Meyer-Baese, Anke; Ganslandt, Oliver; Buchfelder, Michael; Oberndorfer, Stefan (Metabolites, 2022)
Glioblastoma (GB) and brain metastasis (BM) are the most frequent types of brain tumors in adults. Their therapeutic management is quite different and a quick and reliable initial characterization has a significant impact on clinical outcomes. However, the differentiation of GB and BM remains a major challenge in today's clinical neurooncology due to their very similar appearance in conventional magnetic resonance imaging (MRI). Novel metabolic neuroimaging has proven useful for improving diagnostic performance but requires artificial intelligence for implementation in clinical routines. Here; we investigated whether the combination of radiomic features from MR-based oxygen metabolism ("oxygen metabolic radiomics") and deep convolutional neural networks (CNNs) can support reliably pre-therapeutic differentiation of GB and BM in a clinical setting. A self-developed one-dimensional CNN combined with radiomic features from the cerebral metabolic rate of oxygen (CMRO2) was clearly superior to human reading in all parameters for classification performance. The radiomic features for tissue oxygen saturation (mitoPO(2); i.e., tissue hypoxia) also showed better diagnostic performance compared to the radiologists. Interestingly, both the mean and median values for quantitative CMRO2 and mitoPO(2) values did not differ significantly between GB and BM. This demonstrates that the combination of radiomic features and DL algorithms is more efficient for class differentiation than the comparison of mean or median values. Oxygen metabolic radiomics and deep neural networks provide insights into brain tumor phenotype that may have important diagnostic implications and helpful in clinical routine diagnosis.
CRIS-Team WoS Importer:2023-01-27

Endoscope-Assisted Microsurgical Removal of an Optic Foramen Meningioma through a Frontolateral Minicraniotomy - Kurucz, Peter; Opitz, Holger; Buchfelder, Michael; Ganslandt, Oliver (Journal of Neurological Surgery Part B: Skull Base, 2018)
A 72-year-old male patient with visual disturbance of the right eye was diagnosed with a small meningioma of the right optic foramen extending to the carotid cistern. The operation was performed through an individually tailored frontolateral minicraniotomy via a curvilinear skin incision behind the hairline. Endoscope-assisted microsurgical technique was used to resect the lesion. The roof of the optic canal was partly removed to get access to the intraforaminal tumor parts. The lesion could be completely removed and the patient showed a satisfactory visual recovery in the follow-up examinations. The link to the video can be found at: https://youtu.be/p8EZx7aryeQ .
EVALuna2:214806

Endoscope-Assisted Minimally Invasive Microsurgical Removal of a Medium-Sized Acoustic Neuroma (T3a) through a Retrosigmoid Mini-Craniotomy with Preservation of Hearing - Kurucz, Peter; Barany, Laszlo; Buchfelder, Michael; Ganslandt, Oliver (Journal of Neurological Surgery Part B: Skull Base, 2019)
A 45-year-old male patient with reduced hearing in the right ear was diagnosed with a medium-sized (T3a) acoustic neuroma. The operation was performed through an individually tailored retrosigmoid mini-craniotomy. Endoscope-assisted microsurgical technique was applied to early detect the location of the facial and cochlear nerves as well as to look around the hidden corners during the surgery. The entire operation was performed without using brain retractors. The moderate intrameatal extension of the tumor and the use of angled endoscopes allowed to avoid the drilling of the internal auditory meatus. The lesion could be completely removed and the patient showed a satisfactory hearing recovery in the follow-up examinations 3 months after the surgery. The link to the video can be found at: https://youtu.be/dAYLakih924.
CRIS-Team Scopus Importer:2019-06-18
Keywords: acoustic neuroma; endoscope-assisted microsurgery; keyhole approach; minimally invasive; retrosigmoid craniotomy

Endoscopic approach-routes in the posterior fossa cisterns through the retrosigmoid keyhole craniotomy: an anatomical study - Kurucz, Peter; Baksa, Gabor; Patonay, Lajos; Thaher, Firas; Buchfelder, Michael; Ganslandt, Oliver (Neurosurgical Review, 2017)
Endoscopy in cerebellopontine angle surgery is an increasingly used technique. Despite of its advantages, the shortcomings arising from the complex anatomy of the posterior fossa are still preventing its widespread use. To overcome these drawbacks, the goal of this study was to define the anatomy of different endoscopic approaches through the retrosigmoid craniotomy and their limitations by surgical windows. Anatomical dissections were performed on 25 fresh human cadavers to describe the main approach-routes. Surgical windows are spaces surrounded by neurovascular structures acting as a natural frame and providing access to deeper structures. The approach-routes are trajectories starting at the craniotomy and pointing to the lesion, passing through certain windows. Twelve different windows could be identified along four endoscopic approach-routes. The superior route provides access to the structures of the upper pons, lower mesencephalon, and the upper neurovascular complex through the suprameatal, superior cerebellar, and infratrigeminal windows. The supratentorial route leads to the basilar tip and some of the suprasellar structures via the ipsi- and contralateral oculomotor and dorsum sellae windows. The central endoscopic route provides access to the middle pons and the middle neurovascular complex through the inframeatal, AICA, and basilar windows. The inferior endoscopic route is the pathway to the medulla oblongata and the lower neurovascular complex through the accessory, hypoglossal, and foramen magnum windows. The anatomy and limitations of each surgical windows were described in detail. These informations are essential for safe application of endoscopy in posterior fossa surgery through the retrosigmoid approach.
EVALuna2:102200

Essentials in intraoperative indocyanine green videoangiography assessment for intracranial aneurysm surgery: conclusions from 295 consecutively clipped aneurysms and review of the literature - Roessler, Karl; Krawagna, Maximilian; Dörfler, Arnd; Buchfelder, Michael; Ganslandt, Oliver (Neurosurgical Focus, 2014)
Indocyanine green (ICG) videoangiography (VA) in cerebral aneurysm surgery allows confirmation of blood flow in parent, branching, and perforating vessels as well as assessment of remnant aneurysm parts after clip application. A retrospective analysis and review of the literature were conducted to determine the current essential advantages of ICG-VA in aneurysm surgery.The authors retrospectively evaluated all aneurysm cases treated with the aid of intraoperative ICG-VA at a single institution between 2007 and 2013. They also analyzed the literature published since the initial description of ICG-VA in 2003.Two hundred forty-six procedures were performed in 232 patients harboring 295 aneurysms. The patients, whose mean age was 54 years, consisted of 159 women and 73 men. One hundred twenty-four surgeries were performed after subarachnoid hemorrhage, and 122 were performed for incidental aneurysms. Single aneurysms were clipped in 185 patients, and multiple aneurysms were clipped in 47 (mean aneurysm diameter 6.9 mm, range 2-40 mm). No complications associated with ICG-VA occurred. Intraoperative microvascular Doppler ultrasonography was performed before ICG-VA in all patients, and postoperative digital subtraction angiography (DSA) studies were available in 121 patients (52.2%) for retrospective comparative analysis. In 22 (9%) of 246 procedures, the clip position was modified intraoperatively as a consequence of ICG-VA. Stenosis of the parent vessels (16 procedures) or occlusion of the perforators (6 procedures), not detected by micro-Doppler ultrasonography, were the most common problems demonstrated on ICG-VA. In another 11 procedures (4.5%), residual perfusion of the aneurysm was observed and one or more additional clips were applied. Vessel stenosis or a compromised perforating artery occurred independent of aneurysm location and was about equally common in middle cerebral artery and anterior communicating artery aneurysms. In 2 procedures (0.8%), aneurysm puncture revealed residual blood flow within the lesion, which had not been detected by the ICG-VA. In the postoperative DSA studies, unexpected small (< 2 mm) aneurysm neck remnants, which had not been detected on intraoperative ICG-VA, were found in 11 (9.1%) of 121 patients. However, these remnants remained without consequence except in 1 patient with a 6-mm residual aneurysm dome, which was subsequently embolized with coils.In a large cohort of consecutive patients, ICG-VA proved to be a helpful intraoperative tool and led to a significant intraoperative clip modification rate of 15%. However, small, < 2-mm-wide neck remnants and a 6-mm residual aneurysm were missed by intraoperative ICG-VA in up to 10% of patients. Results in this study confirm that DSA is indispensable for postoperative quality assessment in complex aneurysm surgery.
EVALuna2:22828

Evaluation of a novel noninvasive ICP monitoring device in patients undergoing invasive ICP monitoring: preliminary results - Ganslandt, Oliver; Mourtzoukos, Stylianos; Stadlbauer, Andreas; Sommer, Bjoern; Rammensee, Rudolf (Journal of Neurosurgery, 2018)
OBJECTIVE There is no established method of noninvasive intracranial pressure (NI-ICP) monitoring that can serve as an alternative to the gold standards of invasive monitoring with external ventricular drainage or intraparenchymal monitoring. In this study a new method of NI-ICP monitoring performed using algorithms to determine ICP based on acoustic properties of the brain was applied in patients undergoing invasive ICP (I-ICP) monitoring, and the results were analyzed. METHODS In patients with traumatic brain injury and subarachnoid hemorrhage who were undergoing treatment in a neurocritical intensive care unit, the authors recorded ICP using the gold standard method of invasive external ventricular drainage or intraparenchymal monitoring. In addition, the authors simultaneously measured the ICP noninvasively with a device (the HS-1000) that uses advanced signal analysis algorithms for acoustic signals propagating through the cranium. To assess the accuracy of the NI-ICP method, data obtained using both I-ICP and NI-ICP monitoring methods were analyzed with MATLAB to determine the statistical significance of the differences between the ICP measurements obtained using NI-ICP and I-ICP monitoring. RESULTS Data were collected in 14 patients, yielding 2543 data points of continuous parallel ICP values in recordings obtained from I-ICP and NI-ICP. Each of the 2 methods yielded the same number of data points. For measurements at the ≥ 17-mm Hg cutoff, which was arbitrarily chosen for this preliminary analysis, the sensitivity and specificity for the NI-ICP monitoring were found to be 0.7541 and 0.8887, respectively. Linear regression analysis indicated that there was a strong positive relationship between the measurements. Differential pressure between NI-ICP and I-ICP was within ± 3 mm Hg in 63% of data-paired readings and within ± 5 mm Hg in 85% of data-paired readings. The receiver operating characteristic-area under the curve analysis revealed that the area under the curve was 0.895, corresponding to the overall performance of NI-ICP monitoring in comparison with I-ICP monitoring. CONCLUSIONS This study provides the first clinical data on the accuracy of the HS-1000 NI-ICP monitor, which uses advanced signal analysis algorithms to evaluate properties of acoustic signals traveling through the brain in patients undergoing I-ICP monitoring. The findings of this study highlight the capability of this NI-ICP device to accurately measure ICP noninvasively. Further studies should focus on clinical validation for elevated ICP values.
EVALuna2:214803

Flat panel detector angiographic CT for stent-assisted coil embolization of broad-based cerebral aneurysms - Richter, Gregor; Engelhorn, Tobias; Struffert, Tobias; Dölken, Marc; Ganslandt, Oliver; Hornegger, Joachim; Kalender, Willi Alfred; Dörfler, Arnd (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The purpose of this work was to evaluate angiographic CT (ACT) in the combined application of a self-expanding neurovascular stent and detachable platinum coils in the management of broad-based and fusiform intracranial aneurysms. MATERIALS AND METHODS: Eleven patients harboring wide-necked intracranial aneurysms were treated with a flexible self-expanding neurovascular stent and subsequent aneurysm embolization with platinum microcoils. ACT was performed after the interventional procedure to analyze stent position and the relationship of coils to the stent. Postprocessing included multiplanar reconstructions (MPRs) and maximum intensity projections (MIPs). ACT volume datasets were postprocessed for soft tissue visualization. RESULTS: Accurate stent placement with subsequent coil occlusion of the aneurysms was feasible in all of the patients. Similar to nonsubtracted digital subtraction angiography (DSA) images, radiopaque platinum stent markers showed excellent visibility in ACT as well. The stent struts themselves, hardly visible in nonsubtracted DSA, were visible in MPRs and MIPs of ACT in all of the patients. In aneurysms larger than 10 mm in diameter, accurate stent assessment at the level of the coils was limited due to beam hardening artifacts. Postprocedural ACT in all of the patients did not reveal any evidence of procedure-related intracranial hemorrhage. CONCLUSION: ACT provides cross-sectional, 3D visualization of endovascular stents otherwise hardly visible with plain fluoroscopy. ACT enables us to accurately determine stent position, which may be helpful in complex stent-assisted aneurysm coiling procedures. However, in aneurysms larger than 10 mm in diameter, beam hardening artifacts caused by the endoaneurysmal coil package impair visibility of the stent. Further data are necessary to evaluate the usefulness of ACT in stent-assisted aneurysm coiling.

Functional and quantitative magnetic resonance myelography of symptomatic stenoses of the lumbar spine - Eberhardt, Knut; Ganslandt, Oliver Thomas; Stadlbauer, Andreas (Neuroradiology, 2014)
The objective of this study was to demonstrate that functional, quantitative magnetic resonance myelography (MRM) allows standardized diagnosis of symptomatic lumbar spinal stenoses which show at least equal detectability compared to functional myelography and postmyelographic CT (pmCT) based on intra- and postoperative findings.We investigated 43 volunteers and 47 patients with symptomatic lumbar spinal stenoses using MRM in normal position as well as in flexion and extension in a standard whole-body MR scanner. Twenty volunteers were additionally examined under axial loading. All patients were investigated by functional myelography and pmCT and 10 patients had a functional lumbar MRM postoperatively. Range of motion and cerebrospinal fluid (CSF) volumes in normal position, flexion, extension, and under axial loading (volunteers) were assessed for each segment. Detectability was determined by using intraoperative findings, and postoperative freedom of symptoms was correlated with CSF volume changes in MRM.The ranges of motion in a standard whole-body MR scanner provide adequate scope for investigations into function (flexion and extension) in both volunteers and patients. Axial loading was associated with a mechanism of extension, albeit to a far smaller extent. Detectability of lumbar stenoses was 100% for MRM, 58% for conventional myelography, and 68% for pmCT. Postoperative changes in CSF volume of levels with stenoses in MRM strongly correlated with freedom of symptoms (R = 0.772).This MRM method allows for exact diagnosis and reproducible quantification of stenoses, motion-related changes, and spondylolistheses of the lumbar spine. It may be useful for early detection of alterations in order to avoid neuronal compression.
EVALuna2:22847

Improved magnetic resonance myelography of the lumbar spine using image fusion and volumetry - Eberhardt, Knut; Ganslandt, Oliver Thomas; Stadlbauer, Andreas (Journal of Neurosurgery-Spine, 2014)
The goal of this study was to investigate the usefulness and diagnostic potential of an improved MR myelography approach using a dedicated, heavily T2-weighted, 3D MRI sequence in combination with image fusion. A further aim was to compare dural areas and volumes of normal and pathological altered lumbar spine levels, and accuracy in the assessment of the stenoses, with those obtained by postmyelographic CT.Fifty patients underwent myelography, postmyelographic CT, and the improved MR myelography approach using a dedicated, heavily T2-weighted, 3D MRI sequence and image fusion. Dural cross-sectional areas and volumes for normal lumbar levels and levels with stenosis were calculated for postmyelographic CT and MR myelography data. The significant differences and Pearson correlations between dural cross-sectional areas and volumes from L1-2 to L5-S1 of postmyelographic CT and MR myelography were analyzed. The 99% CIs for normal and stenotic levels in patients with claudication distances less than 100 meters were calculated.For both dural areas and volumes in normal lumbar levels, the authors found no significant differences and strong correlations between postmyelographic CT and MR myelography. For the lower lumbar levels (L4-5 and L5-S1) they found significantly larger dural areas on MR myelography compared with postmyelographic CT, but not for the upper levels (L2-3 and L3-4). Dural volume analysis revealed significantly larger volumes for MR myelography at all 4 lumbar levels with stenoses in the cohort (L2-3 to L5-S1). Complete separation with no overlap was found between the 99% CIs for normal levels and stenotic levels.Differences in dural areas and volumes in this study may have been caused by the fact that in the case of a severely compressed thecal sac, the viscosity of the intrathecally applied contrast agent is too high in the framework of myelography. The gravitationally dependent component is thus too low to achieve sufficient fluid contrast. An optimized MR myelography approach-a dedicated 3D MR myelography sequence with high spatial resolution in combination with image fusion-is required to achieve a more reliable diagnosis of lumbar spine stenoses, especially with severe compression, compared with postmyelographic CT. This MR myelography approach may be helpful in preventing overestimation of lumbar spine stenoses. The upper limits of 99% CIs for stenotic levels can be interpreted as an indication for surgical treatment. However, further studies that include postoperative outcomes are required.
EVALuna2:22867

Improved Postoperative Facial Nerve and Hearing Function in Retrosigmoid Vestibular Schwannoma Surgery Significantly Associated with Semisitting Position - Roessler, Karl; Krawagna, Maximilian; Bischoff, Barbara; Rampp, Stefan; Ganslandt, Oliver Thomas; Iro, Heinrich; Schmitt, Hubert; Buchfelder, Michael (World Neurosurgery, 2016)
The pros and cons of semisitting positioning (SSP) versus lateral, horizontal positioning (LP) during retrosigmoid vestibular schwannoma (VS) surgery, especially concerning postoperative cranial nerve and brain stem preservation, are under continuous discussion.In a single-center retrospective cohort study, 30 VSs operated on in SSP compared with 30 operated on in LP with comparable demography were analyzed. During SSP surgery, transesophageal echocardiographic monitoring for venous air embolism was used continuously. Electrophysiologic cranial nerve monitoring was used in both groups.Length of surgery was significantly different between both groups: 183 minutes mean in SSP surgery versus 365 minutes mean in LP surgery (P = 0.0001). Postoperative rates of facial palsy and hearing loss were also significantly different. Six months postoperatively, 63% had normal facial nerve function after SSP surgery, whereas in LP surgery, 40% had no facial palsy (P = 0.02). Hearing preservation rate was also significantly different: 44% in SSP surgery compared with 14% in LP surgery who had preserved hearing (P = 0.006). Because of cerebrospinal fluid leaks, there were 3 operative revisions in the LP group (10%) and 1 (3.3%) in the SSP group. A clinically insignificant venous air embolism rate was found in 3.3% of patients (1/30) during SSP surgery. The neurologic outcome after 6 months was 1.2 on the Rankin Scale in the LP group and 1.0 in the SSP group, with zero mortality.SSP compared with LP surgery was associated with significantly shorter operation time and better facial and cochlear nerve function in VS surgery postoperatively, without differences in complication rate
EVALuna2:16715

Microsurgical anatomy and pathoanatomy of the outer arachnoid membranes in the cerebellopontine angle: cadaveric and intraoperative observations - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Barany, Laszlo (Acta Neurochirurgica, 2023)
Purpose: The cerebellopontine angle (CPA) is a frequent region of skull base pathologies and therefore a target for neurosurgical operations. The outer arachnoid is the key structure to approach the here located lesions. The goal of our study was to describe the microsurgical anatomy of the outer arachnoid of the CPA and its pathoanatomy in case of space-occupying lesions. Methods: Our examinations were performed on 35 fresh human cadaveric specimens. Macroscopic dissections and microsurgical and endoscopic examinations were performed. Retrospective analysis of the video documentations of 35 CPA operations was performed to describe the pathoanatomical behavior of the outer arachnoid. Results: The outer arachnoid cover is loosely attached to the inner surface of the dura of the CPA. At the petrosal surface of the cerebellum the pia mater is strongly adhered to the outer arachnoid. At the level of the dural penetration of the cranial nerves, the outer arachnoid forms sheath-like structures around the nerves. In the midline, the outer arachnoid became detached from the pial surface and forms the base of the posterior fossa cisterns. In pathological cases, the outer arachnoid became displaced. The way of displacement depends on the origin of the lesion. The most characteristic patterns of changes of the outer arachnoid were described in case of meningiomas, vestibular schwannomas, and epidermoid cysts of the CPA. Conclusion: The knowledge of the anatomy of the outer arachnoid of the cerebellopontine region is essential to safely perform microsurgical approaches as well as of dissections during resection of pathological lesions.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Arachnoid; Cerebellopontine angle; Epidermoid cyst; Meningioma; Surgical anatomy; Vestibular schwannoma

Morphometry and microsurgical anatomy of Bochdalek's flower basket and the related structures of the cerebellopontine angle - Barany, Laszlo; Baksa, Gabor; Patonay, Lajos; Ganslandt, Oliver; Buchfelder, Michael; Kurucz, Peter (Acta Neurochirurgica, 2017)
BACKGROUND: Bochdalek's flower basket (Bfb) is the distal part of the horizontal segment of the fourth ventricle's choroid plexus protruding through the lateral aperture (foramen of Luschka). The microsurgical anatomy of the cerebellopontine angle, fourth ventricle and its inner choroid plexus is well described in the literature, but only one radiological study has investigated the Bfb so far. The goal of the present study was to give an extensive morphometric analysis of the Bfb for the first time and discuss the surgically relevant anatomical aspects. METHOD: Forty-two formalin-fixed human brains (84 cerebellopontine angles) were involved in this study. Photomicrographs with scale bars were taken in every step of dissection to perform further measurements with Fiji software. The lengths and widths of the Bfb, rhomboid lip and lateral aperture of the fourth ventricle as well as the related neurovascular and arachnoid structures were measured. The areas of two sides were compared with paired t-tests using R software. Significance level was set at p < 0.05. RESULTS: Protruding choroid plexus was present in 77 cases (91.66%). In 6 cases (7.14%), the Bfb was totally covered by the rhomboid lip, and in one case (1.19%), it was absent. The mean width of the Bfb was 6.618 mm (2-14 mm), the mean height 5.658 mm (1.5-14 mm) and mean area 25.80 mm2 (3.07-109.83 mm2). There was no statistically significant difference between the two sides (p = 0.1744). The Bfb was in contact with 20 AICAs (23.80%), 6 PICAs (7.14%) and 39 vestibulocochlear nerves (46.42%). Arachnoid trabecules, connecting the lower cranial nerves to the Bfb or rhomboid lip, were found in 57 cases (67.85%). CONCLUSIONS: The Bfb is an important landmark during various surgical procedures. Detailed morphology, dimensions and relations to the surrounding neurovascular structures are described in this study. These data are essential for surgeons operating in this region.
EVALuna2:102199

Neural and vascular architecture of the septum pellucidum: an anatomical study and considerations for safe endoscopic septum pellucidotomy - Barany, Laszlo; Meszaros, Cintia; Ganslandt, Oliver; Buchfelder, Michael; Kurucz, Peter (Journal of Neurosurgery, 2020)
OBJECTIVE The septum pellucidum is a bilateral thin membranous structure representing the border between the frontal horns of the lateral ventricles. Its most examined components are the septal veins due to their surgical importance during endoscopic septum pellucidotomy (ESP), which is a well-accepted method for surgical treatment of unilateral hydrocephalus. It is widely accepted that the septum pellucidum contains nerve fibers as well, but interestingly, no anatomical study has been addressed to its neural components before. The aim of the present study was to identify these elements as well as their relations to the septal veins and to define major landmarks within the ventricular system for neurosurgical use. METHODS Nine formalin-fixed human cadaveric brains (18 septa pellucida) were involved in this study. A central block containing both septa pellucida was removed and frozen at -30°C for 2 weeks in 7 cases. The fibers of the septum pellucidum and the adjacent areas including the venous elements were dissected under magnification by using homemade wooden spatulas and microsurgical instruments. In 2 cases a histological technique was used to validate the findings of the dissections. The blocks were sliced, embedded in paraffin, cut in 7-µm-thick slices, and then stained as follows: 1) with H & E, 2) with Luxol fast blue combined with cresyl violet, and 3) with Luxol fast blue combined with Sirius red. RESULTS The septum pellucidum and the subjacent septum verum form the medial wall of the frontal horn of the lateral ventricle. Both structures contain nerve fibers that were organized in 3 groups: 1) the precommissural fibers of the fornix; 2) the inferior fascicle; and 3) the superior fascicle of the septum pellucidum. The area directly rostral to the postcommissural column of the fornix consisted of macroscopically identifiable gray matter corresponding to the septal nuclei. The histological examinations validated the findings of the authors’ fiber dissections. CONCLUSIONS The nerve elements of the septum pellucidum as well as the subjacent septum verum were identified with fiber dissection and verified with histology for the first time. The septal nuclei located just anterior to the fornix and the precommissural fibers of the fornix should be preserved during ESP. Considering the venous anatomy as well as the neural architecture of the septum pellucidum, the fenestration should ideally be placed above the superior edge of the fornix and preferably dorsal to the interventricular foramen.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Endoscopic septum pellucidotomy; Fiber dissection; Hydrocephalus; Klingler method; Septum pellucidum; Surgical anatomy; White matter tracts

Noncurated Data Lead to Misinterpretation of Treatment Outcomes in Patients With Prostate Cancer After Salvage or Palliative Radiotherapy - Rutzner, Sandra; Ganslandt, Oliver Thomas; Fietkau, Rainer; Prokosch, Hans-Ulrich; Lubgan, Dorota (JCO Clinical Cancer Informatics, 2019)
PURPOSE: Clinical data warehouses (cDWHs) and cancer registry databases have enabled researchers to conduct clinical analytics with structured electronic health record data. However, these secondary electronic health record sources are often limited in scope because they do not capture the clinical information needed to understand complex clinical questions. Thus, we evaluated the effect of additional curation of data. MATERIALS AND METHODS: Clinical data sets of 149 patients with prostate cancer with biochemical recurrence after radical prostatectomy treated with salvage or palliative radiotherapy between 2008 and 2017 from our institutional cDWH and Gießener Tumor Documentation System (GTDS) were linked (data warehouse [DWH] population) for analyzing treatment outcomes. The linked data sets were manually curated (manual postprocessing [MPP], eg, incorporate data from established urologists). The primary outcomes were the impact on data quality of treatment outcomes and the time spent on data curation. RESULTS: We obtained significantly more information on disease progression and patient survival (nonsignificant) when using curated data; the biochemical progression-free survival rate at 5 years for the DWH and DWH plus MPP populations was 63% v 30% (P ≤ .001) and the overall survival rate was 84% v 81% (P = .479), respectively. The median deviation of completeness and the median concordance of clinical data values were 21.47% (range, 55.38%-100%) and 95.00% (range, 63.40%-100%), respectively. We spent 121 hours, 42 minutes on data curation, with most time required for laboratory values, accounting, for a total of 45 hours, 20 minutes (37.26%). CONCLUSION: Our analysis indicates that time-to-event outcomes for patients with prostate cancer cannot be extracted using secondary data sources (cDWH plus GTDS) only. Outcomes data differed between the electronic data (DWH) and the second manual extraction (DWH plus MPP) because of a lack of follow-up data. When using such unique database resources, only baseline characteristics can reliably be extracted.
EVALuna2:209482

Optimized angiographic computed tomography with intravenous contrast injection: An alternative to conventional angiography in the follow-up of clipped aneurysms? Clinical article - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver; Saake, Marc; Lücking, Hannes; Rösch, Julie; Knossalla, Frauke; Dörfler, Arnd (Journal of Neurosurgery, 2012)
Object. The purpose of this study was to evaluate the diagnostic accuracy of an optimized angiographic CT (ACT) program with intravenous contrast agent injection (ivACT) in the assessment of potential aneurysm remnants after neurosurgical clipping compared with conventional digital subtraction angiography (DSA). Methods. The authors report on 14 patients with 19 surgically clipped cerebral aneurysms who were scheduled to undergo angiographic follow-up. For each patient, the authors performed ivACT with dual rotational acquisition and conventional angiography including a 3D rotational run. The ivACT and 3D DSA data were reconstructed with different imaging modes, including a newly implemented subtraction mode with motion correction. Thereafter, the data sets were merged by the dual-volume technique, and freely rotatable 3D images were obtained for further analysis. Observed aneurysm remnants were electronically measured and classified for each modality by 2 experienced neuroradiologists. Results. Digital subtraction angiography and ivACT both provided high-quality images without motion artifacts. Artifact disturbances from the aneurysm clips led to a compromised, but still sufficient, image quality in 1 case. The ivACT assessed all aneurysm remnants as true-positive up to a minimal size of 2.6 x 2.4 mm in accordance with the DSA findings. There was a tendency for ivACT to overestimate the size of the aneurysm remnants. All cases without aneurysm remnants on DSA were scored correctly as true-negative by ivACT. Conclusions. By using an optimized image acquisition protocol as well as enhanced postprocessing algorithms, the noninvasive ivACT seems to achieve results comparable to those of conventional angiography in the follow-up of clipped cerebral aneurysms. The authors have shown that ivACT can provide reliable diagnostic information about potential aneurysm remnants after neurosurgical clipping with high sensitivity and specificity, sufficient for clinical decision making, at least for aneurysms in the anterior circulation located distal to the internal carotid artery. These preliminary results may be a promising step to replace conventional angiography by a noninvasive imaging technique in selected cases after aneurysm clipping.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Aneurysm clipping; Angiographic computed tomography; Follow-up imaging; Noninvasive imaging; Vascular disorders

Optimizing contrast-enhanced magnetic resonance imaging characterization of brain metastases: Relevance to stereotactic radiosurgery - Anzalone, Nicoletta; Essig, Marco; Lee, Seung-Koo; Dörfler, Arnd; Ganslandt, Oliver; Combs, Stephanie E.; Picozzi, Piero (Neurosurgery, 2013)
Intracranial metastases are the most common form of intra-axial brain tumor. Management approaches to brain metastases include surgical resection, whole-brain radiotherapy, and stereotactic radiosurgery (SRS). The management approach that is selected is based typically on algorithms that incorporate the number, size, and location of lesions. SRS is the treatment of choice when metastases detected on imaging are few (maximum, 3-5) and/or of small size (≤30 mm) and offers the advantages of noninvasiveness and the ability to treat inaccessible lesions compared with surgical resection. Contrast-enhanced magnetic resonance imaging (MRI) is the standard imaging technique for determining the number, size, and location of metastatic lesions. In SRS, the capability of MRI to delineate lesion borders precisely in 3 dimensions helps reduce recurrence rates and minimize radiation necrosis in surrounding tissue. Optimization of the MRI protocol, including selection of the appropriate gadolinium-based contrast agent (GBCA), is paramount for accurate lesion imaging. GBCAs differ in their safety, tolerability, and efficacy because of their diverse physicochemical properties. Gadobutrol and gadobenate dimeglumine are high-relaxivity GBCAs that demonstrate superior efficacy for imaging metastatic lesions compared with other GBCAs, whereas gadobutrol additionally provides macrocyclic stability. This article reviews recent comparative trials of GBCAs and discusses their relevance for optimizing MRI protocols in the management of brain metastases, with particular relevance to SRS. ABBREVIATIONS:: CNR, contrast-to-noise ratioCNS, central nervous systemGBCA, gadolinium-based contrast agentNSF, nephrogenic systemic fibrosisSRS, stereotactic radiosurgeryWBRT, whole-brain radiotherapy. © 2013 by the Congress of Neurological Surgeons.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain metastases; Gadobutrol; Gadolinium-based contrast media; MRI; Stereotactic radiosurgery

Papillary tumor of the pineal region with anaplastic small cell component - Heim, Stephanie; Coras, Roland; Ganslandt, Oliver; Kufeld, Markus; Blümcke, Ingmar; Paulus, Werner; Hasselblatt, Martin (Journal of Neuro-Oncology, 2013)
CRIS-Team Scopus Importer:2022-08-05

Papilledema and Echographically Detectable Retro-orbital Dilatation of the Sub-arachnoidal Space with open Fontanelle - Six Case Reports - Gusek-Schneider, G. C.; Mardin, Christian Y.; Trollmann, Regina; Eyüpoglu, Ilker Yasin; Ganslandt, Oliver Thomas (Klinische Monatsblätter für Augenheilkunde, 2011)
This paper analyses the case reports for three children in which a papilledema occurred before the age of one year. Furthermore, an analysis is also given of three further case reports for children aged less than one year in which, in spite of open fontanelle, no papilledema was found, however, a dilatation of the sub-arachnoidal space was demonstrated echographically. Even in children less than one year of age in which an open fontanelle still exists and in whom a neuro-paediatric clarification of internal hydrocepalus is made, in spite of opththalmoscopically inconspicuous findings for the papilla an echography is indispensable for the evaluation of the sub-arachnoidal space. Here, the early recognition of a dilatation of the retro-bulbar sub-arachnoidal space can possibly prevent the occurrence of a consecutive optic atrophy. At the present time, the data available do not allow the recommendation of an upper age limit for an echographic examination.
EVALuna2:21040

Parametric color coding of digital subtraction angiography in the evaluation of carotid cavernous fistulas - Gölitz, Philipp; Struffert, Tobias; Lücking, Hannes; Roesch, J.; Knossalla, F.; Ganslandt, Oliver; Deuerling-Zheng, Y.; Dörfler, Arnd (Clinical Neuroradiology, 2013)
Purpose: Angiographic assessment of carotid cavernous fistulas (CCFs) can be complex. Our purpose was to examine whether the use of parametric color coding in the postprocessing of DSA series is advantageous in the evaluation of CCFs. Methods: We enrolled 16 patients with angiographically proven CCFs. Endovascular treatment was performed in 14 cases. For postprocessing of digital subtraction angiography (DSA) series, a newly implemented algorithm of parametric color coding was used, turning sequential images of two-dimensional (2D)-DSA series into a single color-coded image. Angiographic data of initial, interventional, and postinterventional 2D-DSA series were compared with color-coded images. Whether parametric color coding could facilitate evaluation of fistula architecture and provide a more precise estimation of fistula venous drainage patterns as well as whether flow analysis could reveal objective changes during and after treatment were investigated. Results: In 56 % of the cases, parametric color coding was observed to facilitate visualization of fistula angioarchitecture. Estimation of fistula drainage flow patterns was considered to be improved in 31 % of the cases. For assessment of hemodynamic changes during and after treatment, parametric color coding was assumed to be helpful in 21 % of the cases, especially because revealing flow changes that were not visible on 2D-DSA series were now visible. Conclusions: Parametric color coding is a fast application tool that might provide additional support in the angiographic evaluation of CCFs. Visualization of complex fistula architecture could be facilitated, and flow analysis might improve assessment of venous drainage patterns, thereby increasing overall diagnostic confidence. During and after treatment, hemodynamic changes that were not visible on 2D-DSA series could now be depicted. © 2012 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cerebrovascular disease; Digital subtraction angiography; Endovascular treatment; Image postprocessing

Primary Obstruction of the Foramen of Luschka: Anatomy, Histology, and Clinical Significance - Barany, Laszlo; Baksa, Gabor; Patonay, Lajos; Racz, Gergely; Ganslandt, Oliver; Buchfelder, Michael; Kurucz, Peter (World Neurosurgery, 2018)
BACKGROUND: The foramen of Luschka is a natural aperture between the fourth ventricle and the subarachnoid space at the cerebellopontine angle. Membranous closure of this foramen is referred to as primary obstruction. Available information about this variant and its role in the development of the cysts of the posterior fossa is contradictory. METHODS: The macroscopic and histologic features of the obstructed foramina were examined in 61 formalin-fixed human brains (122 foramina). Three rhomboid lips of various sizes with lateral recess were used for comparison. Five postoperative cases of diverticulum of the foramen of Luschka were included in this study, with 1 case presented in detail to illustrate anatomic and histologic findings. RESULTS: Primary obstruction was present in 11 of 122 cases. In 1 case, an enlarged rigid pouch with a thick wall was found. The wall of the membrane in primary obstruction and the rhomboid lip were composed of an inner ependymal, a middle glial, and an outer leptomeningeal layer. CONCLUSIONS: The rhomboid lip is a remnant of the roof of the fourth ventricle. Imperforation of the foramen of Luschka results in a pouch in the cerebellopontine angle that contains choroid plexus (Bochdalek's flower basket) and communicates with the fourth ventricle. This pouch has the potential to grow to a diverticulum and cause clinical symptoms. Based on our clinical observations, detailed radiologic and surgical-anatomic criteria were proposed to support the differential diagnosis of a diverticulum of the foramen of Luschka. Treatment strategies were also suggested.
EVALuna2:214804

Prophylactic nimodipine treatment and improvement in hearing outcome after vestibular schwannoma surgery: a combined analysis of a randomized, multicenter, Phase III trial and its pilot study - Scheller, Christian; Wienke, Andreas; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver Thomas; Bischoff, Barbara; Zenk, Johannes; Engelhorn, Tobias; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; et al. (Journal of Neurosurgery, 2017)
OBJECTIVE In clinical routines, neuroprotective strategies in neurosurgical interventions are still missing. A pilot study (n = 30) and an analogously performed Phase III trial (n = 112) pointed to a beneficial effect of prophylactic nimodipine and hydroxyethyl starch (HES) in vestibular schwannoma (VS) surgery. Considering the small sample size, the data from both studies were pooled. METHODS The patients in both investigator-initiated studies were assigned to 2 groups. The treatment group (n = 70) received parenteral nimodipine (1-2 mg/hour) and HES (hematocrit 30%-35%) from the day before surgery until the 7th postoperative day. The control group (n = 72) was not treated prophylactically. Facial and cochlear nerve functions were documented preoperatively, during the inpatient care, and 1 year after surgery. RESULTS Pooled raw data were analyzed retrospectively. Intent-to-treat analysis revealed a significantly lower risk for hearing loss (Class D) 12 months after surgery in the treatment group compared with the control group (OR 0.46, 95% CI 0.22-0.97; p = 0.04). After exclusion of patients with preoperative Class D hearing, this effect was more pronounced (OR 0.38, 95% CI 0.17-0.83; p = 0.016). Logistic regression analysis adjusted for tumor size showed a 4 times lower risk for hearing loss in the treatment group compared with the control group (OR 0.25, 95% CI 0.09-0.63; p = 0.003). Facial nerve function was not significantly improved with treatment. Apart from dose-dependent hypotension (p < 0.001), the study medication was well tolerated. CONCLUSIONS Prophylactic nimodipine is safe and may be recommended in VS surgery to preserve hearing. Prophylactic neuroprotective treatment in surgeries in which nerves are at risk seems to be a novel and promising concept. Clinical trial registration no.: DRKS 00000328 ( https://drks-neu.uniklinik-freiburg.de/drks_web/ ).
EVALuna2:33133

Prophylactic nimodipine treatment for cochlear and facial nerve preservation after vestibular schwannoma surgery: a randomized multicenter Phase III trial - Scheller, Christian; Wienke, Andreas; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver Thomas; Bischoff, Barbara; Zenk, Johannes; Engelhorn, Tobias; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; et al. (Journal of Neurosurgery, 2016)
OBJECT A pilot study of prophylactic nimodipine and hydroxyethyl starch treatment showed a beneficial effect on facial and cochlear nerve preservation following vestibular schwannoma (VS) surgery. A prospective Phase III trial was undertaken to confirm these results. METHODS An open-label, 2-arm, randomized parallel group and multicenter Phase III trial with blinded expert review was performed and included 112 patients who underwent VS surgery between January 2010 and February 2013 at 7 departments of neurosurgery to investigate the efficacy and safety of the prophylaxis. The surgery was performed after the patients were randomly assigned to one of 2 groups using online randomization. The treatment group (n = 56) received parenteral nimodipine (1-2 mg/hr) and hydroxyethyl starch (hematocrit 30%-35%) from the day before surgery until the 7th postoperative day. The control group (n = 56) was not treated prophylactically. RESULTS Intent-to-treat analysis showed no statistically significant effects of the treatment on either preservation of facial nerve function (35 [67.3%] of 52 [treatment group] compared with 34 [72.3%] of 47 [control group]) (p = 0.745) or hearing preservation (11 [23.4%] of 47 [treatment group] compared with 15 [31.2%] of 48 [control group]) (p = 0.530) 12 months after surgery. Since tumor sizes were significantly larger in the treatment group than in the control group, logistic regression analysis was required. The risk for deterioration of facial nerve function was adjusted nearly the same in both groups (OR 1.07 [95% CI 0.34-3.43], p = 0.91). In contrast, the risk for postoperative hearing loss was adjusted 2 times lower in the treatment group compared with the control group (OR 0.49 [95% CI 0.18-1.30], p = 0.15). Apart from dose-dependent hypotension (p < 0.001), no clinically relevant adverse reactions were observed. CONCLUSIONS There were no statistically significant effects of the treatment. Despite the width of the confidence intervals, the odds ratios may suggest but do not prove a clinically relevant effect of the safe study medication on the preservation of cochlear nerve function after VS surgery. Further study is needed before prophylactic nimodipine can be recommended in VS surgery.
EVALuna2:22832

Prophylactic nimodipine treatment improves hearing outcome after vestibular schwannoma surgery in men: a subgroup analysis of a randomized multicenter phase III trial. - Scheller, Christian; Rampp, Stefan; Leisz, Sandra; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; Pedro, Maria T.; Rohde, Veit; et al. (Neurosurgical Review, 2021)
A 2016 published randomized multicenter phase III trial of prophylactic nimodipine treatment in vestibular schwannoma surgery showed only a tendency for higher hearing preservation rates in the treatment group. Gender was not included in statistical analysis at that time. A retrospective analysis of the trial considering gender, preoperative hearing, and nimodipine treatment was performed. The treatment group received parenteral nimodipine from the day before surgery until the seventh postoperative day. The control group was not treated prophylactically. Cochlear nerve function was determined by pure-tone audiometry with speech discrimination preoperatively, during in-patient care, and 1 year after surgery and classified according to the Gardner-Robertson grading scale (GR). Logistic regression analysis showed a statistically significant effect for higher hearing preservation rates (pre- and postoperative GR 1-4) in 40 men comparing the treatment (n = 21) and the control (n = 19) groups (p = 0.028), but not in 54 women comparing 27 women in both groups (p = 0.077). The results were also statistically significant for preservation of postoperative hearing with pre- and postoperative GR 1-3 (p = 0.024). There were no differences in tumor sizes between the treatment and the control groups in men, whereas statistically significant larger tumors were observed in the female treatment group compared with the female control group. Prophylactic nimodipine is safe, and an effect for hearing preservation in 40 men with preoperative hearing ability of GR 1-4 was shown in this retrospective investigation. The imbalance in tumor size with larger tumors in females of the treatment group may falsely suggest a gender-related effect. Further investigations are recommended to clarify whether gender has impact on nimodipine's efficacy.
EVALuna2:347977

Sporadic endolymphatic sac tumor–a diagnostic and therapeutic challenge - Kuenzel, Julian; Agaimy, Abbas; Hornung, Joachim; Lell, Michael; Ganslandt, Oliver Thomas; Semrau, Sabine; Zenk, Johannes (International Journal of Clinical and Experimental Pathology, 2014)
Endolymphatic sac tumor (ELST) is a rare low-grade locally aggressive neoplasm of the inner ear that may occur sporadically or in the setting of von Hippel-Lindau syndrome. We herein present a case of sporadic ELST in a 39-year-old man, treated using an interdisciplinary approach (surgery+radiotherapy), with a 10-year follow-up. The patient presented with hearing loss of sudden onset. The treatment of choice for ELST is radical tumor resection, which is associated with a good long-term prognosis. Remission may last for years, but there may be local recurrences, probably as a result of incomplete resection. Adjuvant radiotherapy is an option in case of recurrence and could be discussed after incomplete resection. The purpose of this report is to call attention to ELSTs, which are difficult to diagnose due to their rarity and variety of presentations.
EVALuna2:6593

Stellate Ganglion Block and Intraarterial Spasmolysis in Patients with Cerebral Vasospasm: A Retrospective Cohort Study - Wendel, Christopher; Oberhauser, Cornelia; Schiff, Jan; Henkes, Hans; Ganslandt, Oliver Thomas (Neurocritical Care, 2023)
Background: In patients with symptomatic cerebral vasospasm (CV) following aneurysmal subarachnoid hemorrhage who do not respond to medical therapy, urgent treatment escalation has been suggested to be beneficial for brain tissue at risk. In our routine clinical care setting, we implemented stellate ganglion block (SGB) as a rescue therapy with subsequent escalation to intraarterial spasmolysis (IAS) with milrinone for refractory CV. Methods: In this retrospective analysis from 2012 to 2021, patients with CV following aneurysmal subarachnoid hemorrhage who received an SGB or IAS were identified. Patients were assessed through neurological examination and transcranial Doppler. Rescue therapy was performed in patients with mean cerebral blood flow velocity (CBFV) ≥ 120 cm/s and persistent neurological deterioration/intubation under induced hypertension. Patients were reassessed after therapy and the following day. The Glasgow Outcome Scale was assessed at discharge and 6-month follow-up. Results: A total of 82 patients (mean age 50.16 years) with 184 areas treated with SGB and/or IAS met the inclusion criteria; 109 nonaffected areas were extracted as controls. The mean CBFV decrease in the middle cerebral artery on the following day was − 30.1 (± 45.2) cm/s with SGB and − 31.5 (± 45.2) cm/s with IAS. Mixed linear regression proved the significance of the treatment categories; other fixed effects (sex, age, aneurysm treatment modality [clipping or coiling], World Federation of Neurological Surgeons score, and Fisher score) were insignificant. In logistic regression, the presence of cerebral infarction on imaging before discharge from the intensive care unit (34/82) was significantly associated with unfavorable outcomes (Glasgow Outcome Scale ≤ 3) at follow-up. Conclusions: Stellate ganglion block and IAS decreased CBFV the following 24 h in patients with CV. We suggest SGB alone for patients with mild symptomatic CV (CBFV < 180 cm/s), while subsequent escalation to IAS proved to be beneficial in patients with refractory CV and severe CBFV elevation (CBFV ≥ 180 cm/s).
CRIS-Team Scopus Importer:2023-08-11
Keywords: Cerebral vasospasm; Chemical angioplasty; Delayed cerebral ischemia; Delayed ischemia; Intraarterial spasmolysis; SGB; Stellate ganglion block; Subarachnoid hemorrhage

The Clival Line as an Important Arachnoid Landmark During Endoscopic Third Ventriculostomy: An Anatomic Study - Kurucz, Peter; Barany, Laszlo; Buchfelder, Michael; Ganslandt, Oliver (World Neurosurgery, 2018)
OBJECTIVE: Endoscopic third ventriculostomy (ETV) is a well-accepted treatment option instead of ventriculoperitoneal shunt placement in cases of obstructive hydrocephalus. A sufficient flow from the ventricles to the basal cisterns requires perforation of the arachnoid membranes in the retroclival region. This point is critical to achieve an optimal outcome. The complex arachnoid relations were investigated in the retroclival region from the viewpoint of ETV, and anatomic landmarks were defined for subarachnoid dissections. METHODS: Sixty fresh human cadaveric specimens were dissected under macroscopic, microscopic, and endoscopic control. The recordings of 100 operated cases of ETVs were analyzed to ascertain the clinical-anatomic relevance. RESULTS: The Liliequist membrane complex and the anterior pontine membranes are located just above and parallel to both sides of the basilar artery. The basal attachment of these membranes forms an inverted U-shaped, white-grey thickening on the outer arachnoid. We refer to this structure as the clival line. During ETV, if arachnoid dissections were performed ventrally to the clival line, the outer arachnoid was opened; this resulted in a limited flow to the subarachnoid spaces (ventriculo-subdural). If the perforation on the arachnoid membranes was dorsal to the clival line, the prepontine cistern could be directly reached through the Liliequist membrane complex. CONCLUSIONS: Sufficient arachnoid dissection is essential for a successful ETV. The clival line is an important landmark that helps to perform the subarachnoid dissections correctly and achieve an undisrupted cerebral spinal fluid flow between the ventricles and the basal cisterns.
EVALuna2:214797

The “Valva Cerebri”: Morphometry, Topographic Anatomy and Histology of the Rhomboid Membrane at the Craniocervical Junction - Kurucz, Peter; Meszaros, Cintia; Ganslandt, Oliver; Buchfelder, Michael; Barany, Laszlo (Clinical Anatomy, 2020)
The arachnoid membranes' anatomy is a controversial topic in the literature, and the rhomboid membrane at the craniovertebral junction is an element of this system that has been described poorly. Hence, the objective of our study was to examine this membrane's anatomy and histology. A total of 45 fresh formalin-fixed human cadaveric heads were examined, and anatomic dissections and histologic examinations using standard staining methods were performed. The membrane was found to be a constant structure. It has a rhomboid shape and is located on the medulla oblongata and upper cervical spine's ventral surface within the subarachnoid space. Its average craniocaudal length is 49 mm and the short axis is 26 mm. The cranial apex is attached to the vertebral arteries' junction, and the caudal apex reaches the level of C4. The lateral apices are attached to the dura mater at the level of the denticulate ligament's second insertion. The C1 spinal nerves perforate the membrane, while the C2 roots are located dorsal to it. The membrane is attached strongly to the underlying pia mater. Histologically, it has a typical arachnoid structure, in which its adhesions to the vertebral arteries as well as to the pia mater could be verified histologically. This is the first detailed examination of the rhomboid membrane. Our results suggest that the membrane serves a valve-like function between the spinal and cranial subarachnoid spaces. Based on our findings, further hydrodynamic studies should clarify the membrane's physiological role. Clin. Anat., 2019. © 2019 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2019-09-17

Topographical anatomy of the septum verum and its white matter connections - Barany, Laszlo; Meszaros, Cintia; Alpar, Alan; Ganslandt, Oliver; Hore, Nirjhar; Delev, Daniel; Schnell, Oliver; Kurucz, Peter (Scientific Reports, 2024)
The human septum verum represents a small but clinically important region of the brain. Based on the results of animal experiments, the stimulation of its medial part was recently proposed with various indications like epilepsy or cognitive impairment after traumatic brain injury. The aim of our study was to present the anatomical relationships of the human septum verum using fiber dissection and histological analysis to support its research and provide essential information for future deep brain stimulation therapies. 16 human cadaveric brains were dissected according to Klingler’s method. To validate our macroscopical findings, 12 samples obtained from the dissected brains and 2 additional specimens from unfrozen brains were prepared for histological examinations. We identified the following white matter connections of the septum verum: (1) the precommissural fibers of the fornix; (2) the inferior fascicle of the septum pellucidum; (3) the cingulum; (4) the medial olfactory stria; (5) the ventral amygdalofugal pathway; (6) the stria medullaris of the thalamus and (7) the stria terminalis. Moreover, we could distinguish a less-known fiber bundle connecting the postcommissural column of the fornix to the stria medullaris of the thalamus and the anterior thalamic nuclei. In this study we present valuable anatomical information about this region to promote safe and effective deep brain stimulation therapies in the future.
CRIS-Team Scopus Importer:2024-08-16

Topographical anatomy of the subthalamic region with special interest in the human medial forebrain bundle - Meszaros, Cintia; Kurucz, Peter; Baksa, Gabor; Alpar, Alan; Ganslandt, Oliver; Brandner, Sebastian; Barany, Laszlo (Journal of Neurosurgery, 2024)
OBJECTIVE The medial forebrain bundle (MFB) is a novel promising deep brain stimulation (DBS) target in severe affective disorders that courses through the subthalamic region according to tractography studies. Its potential therapeutic role arose in connection with the development of hypomania during stimulation of the subthalamic nucleus (STN) in Parkinson's disease, offering an alternative explanation for the occurrence of this side effect. However, until now its course exclusively described by tractography had not yet been confirmed by any anatomical method. The aim of this study was to fill this gap as well as to provide a detailed description of the fiber tracts surrounding the STN to facilitate a better understanding of the background of side effects occurring during STN DBS. METHODS Ten human cadaveric brains (20 hemispheres) and 100 healthy subjects (200 hemispheres) from the S500 Release of the Human Connectome Project were involved in this study. Nineteen hemispheres were dissected according to Klingler's method. One additional hemisphere was prepared for histological examinations to validate the macroscopical results and stained with neurofibril silver impregnation according to Krutsay. The authors also aimed to reconstruct the MFB using tractography and correlated the results with their dissections and histological findings. RESULTS The white matter connections coursing through the subthalamic region were successfully dissected. The ansa lenticularis, lenticular fasciculus, thalamic fasciculus, ipsi- and contralateral cerebellar fibers, and medial lemniscus were revealed as closely related fiber tracts to the STN. However, the existence of a distinct fiber bundle corresponding to the MFB described by tractography could not be identified. Using tractography, the authors showed that the depiction of the streamlines representing the MFB was also strongly dependent on the threshold parameters. CONCLUSIONS According to this study's findings, the streamlines of the MFB described by tractography arise from the limitations of the diffusion-weighted MRI fiber tracking method and actually correspond to subthalamic fiber bundles, especially the ansa lenticularis and lenticular fasciculus, which erroneously continue in the anterior limb of the internal capsule, toward the prefrontal cortex.
CRIS-Team Scopus Importer:2024-08-16
Keywords: anatomy; deep brain stimulation; fiber dissection; functional neurosurgery; medial forebrain bundle; subthalamus; tractography